Prospective analysis of neuropsychiatric events in an international disease inception cohort of patients with systemic lupus erythematosus. Issue 3 (8th April 2009) - Hanly, J G; Urowitz, M B; Su, L; Bae, S C; Gordon, C; Wallace, D J; Clarke, A; Bernatsky, S; Isenberg, D; Rahman, A; Alarcón, G S; Gladman, D D; et al.
Abstract : Objectives: To determine the frequency, accrual, attribution and outcome of neuropsychiatric (NP) events and impact on quality of life over 3 years in a large inception cohort of patients with systemic lupus erythematosus (SLE). Methods: The study was conducted by the Systemic Lupus International Collaborating Clinics. Patients were enrolled within 15 months of SLE diagnosis. NP events were identified using the American College of Rheumatology case definitions, and decision rules were derived to determine the proportion of NP disease attributable to SLE. The outcome of NP events was recorded and patient-perceived impact determined by the SF-36. Results: 1206 patients (89.6% female) with a mean (±SD) age of 34.5±13.2 years were included in the study. The mean disease duration at enrolment was 5.4±4.2 months. Over a mean follow-up of 1.9±1.2 years, 486/1206 (40.3%) patients had ≥1 NP events, which were attributed to SLE in 13.0–23.6% of patients using two a priori decision rules. The frequency of individual NP events varied from 47.1% (headache) to 0% (myasthenia gravis). The outcome was significantly better for those NP events attributed to SLE, especially if they occurred within 1.5 years of the diagnosis of SLE. Patients with NP events, regardless of attribution, had significantly lower summary scores for both mental and physical health over the study. Conclusions: NP events in patients with SLE are of variable frequency, most commonly present early in the disease course and adversely impact patients' quality of life over time. Events attributed to non-SLE causes are more common than those due to SLE, although the latter have a more favourable outcome.